PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA WANPRESTASI TERHADAP PERJANJIAN YANG DI WAARMEKING (ANALISIS PUTUSAN NOMOR 240/PDT.G/2021/PN.MDN) - Lailaturahmah, Nabila; Madjid, Neni Vesna; Viana, Wira Okta; Yulinda, Kiki (Ensiklopedia of Journal, 2025)
Abstract: Article 1238 of the Civil Code states that a debtor is considered negligent in fulfilling his obligations. Breach of a waarmeking agreement is regulated in Article 15 Paragraph (2) letter b of Law Number 2 of 2014 concerning the Position of Notary. There are times when a waarmeking agreement gives rise to problems in terms of breach of contract, thus harming one of the parties to the agreement, such as the case decided by the judge with decision number 240/Pdt.G/2021/PN.Mdn. The formulation of the problem in this thesis is: First, How does the judge consider in deciding the case of breach of contract against the case of breach of contract waarmeking in Decision Number 240/Pdt.G/2021/PN.Mdn? Second, What are the legal consequences of Decision Number 240/Pdt.G/2021/PN.Mdn in the case of breach of contract waarmeking? This research is descriptive in nature. The approach used is a normative juridical approach, conducting in-concreto legal research on Decision Number 240/Pdt.G/2021/PN.Mdn. The data used is secondary data obtained through library research or document studies. The data is then analyzed qualitatively and presented in qualitative descriptive form. From the results of the research and discussion, it was concluded that, First, the judge's consideration in deciding the case of default against the default case agreement that was waarmeking based on Decision Number 240 / Pdt.G / 2021 / PN. Mdn, namely legal considerations based on evidence of letters submitted by the Plaintiff in the form of a Debt Acknowledgement Letter that had been Waarmerking Number: 1868 / W / 2021 dated March 2, 2021 at the Notary Office of San Smith, S.H in Medan. However, the Defendant neglected his obligations to the Plaintiff. In addition, there is also evidence of 2 (two) witnesses Joni Iskandar and witness Khairul Rahman, who knew about the debt problem between the Plaintiff and the Defendant. Second, the legal consequences of the decision Number 240 / Pdt.G / 2021 / PN.Mdn in the case of default on the agreement that was waarmeking, namely the judge's decision must be implemented if the parties do not make an appeal to the High Court. The judge's decision in this case is that the Defendant pays all his debts starting from January 5, 2019 until now amounting to Rp. 4,000,000,000,- (four billion rupiah) in cash to the Plaintiff according to the Debt Acknowledgement Letter that has been Waarmeking Number: 1868 / W / 2021 dated March 2, 2021 at the Notary office of San Smith, S.H in Medan and the Defendant pays the court costs determined by the Medan District Court in the amount of Rp. 560,000.00 (Five hundred and sixty thousand rupiah). Keywords: Decision, Rights, Plaintiff's.